Comprehensive effects of galantamine and cilostazol combination therapy on patients with Alzheimer's disease with asymptomatic lacunar infarction. Issue 10 (31st August 2016) - Hishikawa, Nozomi; Fukui, Yusuke; Sato, Kota; Ohta, Yasuyuki; Yamashita, Toru; Abe, Koji
Abstract : Aim: The coexistence of Alzheimer's disease (AD) and cerebrovascular disease pathology increases age‐dependently. We comprehensively analyzed the clinical effects of galantamine or cilostazol monotherapy to the add‐on combination therapy on three major factors of dementia, such as cognitive, affective and activities of daily living functions in AD patients with asymptomatic lacunar infarction. Methods: We divided 101 AD patients with asymptomatic lacunar infarction into two subgroups: group A ( n  = 61, first treated with galantamine and then cilostazol added) and group B ( n  = 40, first treated with cilostazol and galantamine added). We compared the clinical effects before and after combination therapy of galantamine and cilostazol (i.e. 3 months [M] before (–3 M), baseline (0 M), 3 and 6 M after the add‐on combination). Results: Galantamine monotherapy increased cognitive Hasegawa dementia score‐revised scores, which were further improved with add‐on cilostazol. Cilostazol monotherapy also increased the cognitive tests, which were further improved with add‐on galantamine. Add‐on cilostazol significantly improved Geriatric Depression Scale and Abe's behavioral and psychological symptoms of dementia scores after galantamine monotherapy. Cilostazol monotherapy also significantly improved Geriatric Depression Scale scores, with further improvements in Geriatric Depression Scale, apathy scores and Abe's behavioral and psychological symptoms of dementia scores by add‐on galantamine. Activities of daily living scores continuously improved with galantamine monotherapy and add‐on cilostazol. Conclusions: The present study provides a clinical possibility that galantamine or cilostazol monotherapy and the combination therapy maintained or even improved cognitive, affective, and activities of daily living functions in AD with asymptomatic lacunar infarction.Geriatr Gerontol Int 2017; 17: 1384–1391.